2004
DOI: 10.1007/s00268-004-7708-6
|View full text |Cite
|
Sign up to set email alerts
|

Quick Intraoperative Parathyroid Hormone Assay: Surgical Adjunct to Allow Limited Parathyroidectomy, Improve Success Rate, and Predict Outcome

Abstract: Intraoperative parathyroid hormone (PTH) assay (QPTH) has made possible less invasive operative approaches in the treatment of primary hyperparathyroidism with stated advantages. When compared to the traditional bilateral neck exploration (BNE), only the targeted, hypersecreting gland is excised, leaving in situ non-visualized but normally functioning parathyroids. The QPTH-guided limited parathyroidectomy (LPX) must be able to identify multiglandular disease (MGD), predict a successful outcome, and have a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(133 citation statements)
references
References 18 publications
3
127
0
3
Order By: Relevance
“…These statements were based on a recent large number of operations that showed no obvious differences in the success or complication rates between traditional neck explorations or modern, minimally invasive techniques. Primary parathyroidectomy (PTX) is usually reported to have a cure rate of 95-98% and a complication rate as low as 1-3%, with a serious complication rate far below 1% (41)(42)(43). The operative results reported from centres of excellence, however, may be difficult to obtain for routine clinical practice in non-specialised surgical departments.…”
Section: The Success Of and Complications From Surgerymentioning
confidence: 99%
“…These statements were based on a recent large number of operations that showed no obvious differences in the success or complication rates between traditional neck explorations or modern, minimally invasive techniques. Primary parathyroidectomy (PTX) is usually reported to have a cure rate of 95-98% and a complication rate as low as 1-3%, with a serious complication rate far below 1% (41)(42)(43). The operative results reported from centres of excellence, however, may be difficult to obtain for routine clinical practice in non-specialised surgical departments.…”
Section: The Success Of and Complications From Surgerymentioning
confidence: 99%
“…However, 24-27% of preoperative imaging results are discordant (6,16) and 12-18% are negative (17,18,19); for these cases, the gold standard for surgery remains bilateral exploration (5). The choice between the treatment strategies of focused parathyroidectomy and bilateral exploration remains a matter of debate (20,21,22,23). However, recent data in the literature suggested that focused parathyroidectomy was less expensive and induced fewer side effects with at least identical remission rates, resulting in a shorter hospital stay (5,24).…”
Section: Introductionmentioning
confidence: 99%
“…With a 97% accuracy rate, IoPTH is measured based on a 50% drop from an initial PTH level reading to the level measured 10 min after gland excision. When PTH levels remain elevated after an excision of the suspected gland, a bilateral neck exploration may be necessary to locate the remaining hypersecreting tissue [56,57]. The IoPTH test is also reliable in mild cases, even if PTH is not elevated [59].…”
Section: Differential Diagnosis and Work-upmentioning
confidence: 99%
“…The IoPTH assay is used to determine the appropriateness of a parathyroid tissue resection [56,57]. Numerous criteria have been suggested to confirm the sufficiency of parathyroid resections [58]; however, the most widely accepted is the Miami criterion.…”
Section: Differential Diagnosis and Work-upmentioning
confidence: 99%